Effect of Substrate Concentration to Anode Chamber Performance in Microbial Electrolysis Cell - Libertus Darus (Universitas Gadjah Mada, 2011)
Microbial electrolysis is a promising process for bio-hydrogen production which might be implemented in waste water treatment in a near future. Unfortunately substrate could be converted into methane by acetoclastic methanogens and will reduce the coulombic efficiency (CE). The research objective was to study the competition between electrogens and methanogens for substrate in a continuous Microbial Electrolysis Cell (MEC).The competition was studied in relation to controlling acetate influent concentration (Cin) from 35 to 1 mM with a fixed anode potential -350 mV, by assessing activity of electrogens as current density (CD), activity of acetoclastic methanogens as methanogenic consumed acetate (Cmeth), and CE and by measuring anolyte protein content to confirm a steady state condition. Controlling Cin from 35 to 1 mM resulted in tendency of both CD and Cmeth to decrease and CE to increase. At decreasing Cin from 35 to 5 mM which left excess acetate concentration in anolyte, the CEs were between 36.4% and 75.3%. At further decreasing Cin to 1 mM the acetate concentration was limited (Cef 0 mM), but the CE only reached 95.8%. Methanogenesis always occur and electrogens were not able to outcompete the acetoclastic methanogens even though the substrate concentration was limited.Keywords : microbial electrolysis cell, bio-hydrogen, metanogenesis, substrate concentration